2016
DOI: 10.1089/thy.2015.0390
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Registry for Thyroid Incidentalomas: Lessons Learned and the Path Forward

Abstract: Background: Incidentalomas are findings on an imaging test done for other reasons, for which there are no matching symptoms in the patient. They are common in the adrenal gland, pancreas, liver, and thyroid, among other sites. Incidentalomas are a problem because we have a limited understanding of their natural history: it is difficult to know how much of a threat they pose to individual patients. An observational registry that would allow a systematic study of thyroid incidentalomas could reveal their natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Incidentalomas are findings on an imaging test performed for other reasons, for which there are no matching symptoms in the patient (Davies et al 2016 ). Published reports estimated the prevalence of thyroid incidentalomas on [ 18 F]FDG-PET images between 1.2% and 4.3% (Rigo et al 1996 ; Mitchell and Parangi 2005 ; Liu et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incidentalomas are findings on an imaging test performed for other reasons, for which there are no matching symptoms in the patient (Davies et al 2016 ). Published reports estimated the prevalence of thyroid incidentalomas on [ 18 F]FDG-PET images between 1.2% and 4.3% (Rigo et al 1996 ; Mitchell and Parangi 2005 ; Liu et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the overall incidence of thyroid incidentalomas detected on PET imaging is low, the chance of malignancy among incidentalomas detected by [ 18 F]FDG is higher than incidental nodules discovered with other imaging modalities, with a chance for malignancy ranging from 14 to 59% (Gavriel et al 2015 ; Lee et al 2014 ; Demir et al 2016 ; Chun et al 2015 ; Are et al 2007 ; Pagano et al 2011 ; Cohen et al 2001 ; Nilsson et al 2011 ). Nonetheless, we have a limited understanding of the incidentaloma natural history (Davies et al 2016 ). Therefore, the differentiation between malignant and benign thyroid lesions is crucial to avoid unnecessary procedures, to improve the quality of life of patients, and to reduce healthcare costs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed a wide range of prevalence of thyroid incidentalomas detected from CT scans, varying from <1% to 16% [ 4 , 5 , 27-29 ]. The higher prevalence is due to the dedicated imaging reviews of thyroid lesions [ 4 , 5 ], similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence is due to the dedicated imaging reviews of thyroid lesions [ 4 , 5 ], similar to our study. In contrast, the larger database studies (∼100 000 imaging studies) identified thyroid incidentaloma with a <1% reported rate due to routine radiology reports in clinical practice [ 27 , 29 ]. The different rate of incidental detection of a thyroid nodule is 10% when comparing routine reports and dedicated reviews [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 0.4% of imaging studies of the head and neck resulted in a radiologist reporting an incidental thyroid nodule and only 0.03% of studies resulted in a confirmed diagnosis of thyroid cancer [9]. Interestingly a second study done at an institution in a completely different geographic region of the USA also reviewed roughly 100,000 imaging studies and found a thyroid incidentaloma reporting prevalence of 0.1% [10]. This is strikingly similar to our finding and is also in stark contrast to previous studies that estimate the number of thyroid incidentalomas on imaging studies to be between 6 and 33% [1,11,12].…”
mentioning
confidence: 99%